Effects of Mass Media and Digital Media Internet on Young Voter Participation - Christina Natalia Jesica; R. Widya S Sumadinata; Caroline Paskarina (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2020)
Voter participation indicates the success or failure of a general election. People of Bandung City, who have been characterized as an urban society, openly accept mass media as an information channel and the internet as a form of information technology development. In terms of quantity, young voters have potential as a major group of voters in the General Election. The number of young voters in Bandung City achieves 29.6% of the voters on the list (Daftar Pemilih Tetap/DPT or List of Voters) in the Election of Mayor and Deputy Mayor of Bandung in 2018. The lives of the young generation are closely related to the development of media. In this context, therefore, the authors researched to find out if there is a significant effect of print media, electronic media, and internet media on the participation of young voters in Bandung. This article is written based on a survey of 100 respondents aged 17-year-old (married/had been married) up to 30-year-old, who is registered on the List of Voters or DPT in the Election of Mayor and Deputy Mayor of Bandung in 2018. This research uses an instrument named The Ordinal Scale whose validity and reliability have been proven. The research applies a technique Multiple Linear Regression to analyze data, as well as in examining hypothesis. The research findings reveal that print media and electronic media did not have a significant effect on young voters but did the internet media have a necessary effect on the young voters.